Pengaruh Pelatihan dan Kinerja Terhadap Produktivitas Kerja Karyawan Pada Badan Pertanahan Nasional Jakarta Timur - Nabilla Yusman; Irwin Sukrisno Sugeng (Jurnal Portofolio : Jurnal Manajemen dan Bisnis, 2023)
With the implementation of correct and appropriate training, companies can improve the performance of employees in achieving predetermined work productivity. This study aims to determine how big the "The effect of training and performance on employee work productivity in Badan Pertanahan Nasional East Jakarta". The method in this study is quantitative, a type of research that is structured with a clear aim to be able to validate the problem that has been determined. The number of respondents to the research at the East Jakarta National Land Agency was 41 people. Based on the results of the multiple regression test, the regression coefficient value for Training = 0.363 this means that if the respondents' responses regarding Training increase by one unit, it will be able to increase Work Productivity, then the coefficient value regression for performance = 0.837, this means that if performance is increased by one unit it will directly affect the increase in work productivity. Then it was found that the value of R = 0.766 which means that the relationship between training and performance has a strong relationship to increasing work productivity because the value of R = 87.5%, while the magnitude of the coefficient of determination (R2) is 0.766 which means the variability of work productivity variables which can be explained by the variability training and performance that is equal to 75.3%.